2007
DOI: 10.1002/jbm.a.31192
|View full text |Cite
|
Sign up to set email alerts
|

Biocorrosion investigation of two shape memory nickel based alloys: Ni‐Mn‐Ga and thin film NiTi

Abstract: Thin film nitinol and single crystal Ni-Mn-Ga represent two new shape memory materials with potential to be used as percutaneously placed implant devices. However, the biocompatibility of these materials has not been adequately assessed. Immersion tests were conducted on both thin film nitinol and single crystal Ni-Mn-Ga in Hank's balanced salt solution at 37 degrees C and pH 7.4. After 12 h, large pits were found on the Ni-Mn-Ga samples while thin film nitinol displayed no signs of corrosion. Further electroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Similar results with respect to better pitting resistance of electropolished surface conditions compared to mechanically polished or thermally oxidized surfaces have been observed or reported by others [38,43,45,46,51,[63][64][65]. Stephan et al performed electrochemical tests on thinfilm NiTi that demonstrated that as-deposited thin films of NiTi have breakdown potentials superior to a mechanically polished NiTi and suggested passivation or electropolishing of thin-film NiTi may be unnecessary to promote corrosion resistance in vivo [66].…”
Section: B3 Niti Crevice and Pitting Corrosionsupporting
confidence: 57%
See 2 more Smart Citations
“…Similar results with respect to better pitting resistance of electropolished surface conditions compared to mechanically polished or thermally oxidized surfaces have been observed or reported by others [38,43,45,46,51,[63][64][65]. Stephan et al performed electrochemical tests on thinfilm NiTi that demonstrated that as-deposited thin films of NiTi have breakdown potentials superior to a mechanically polished NiTi and suggested passivation or electropolishing of thin-film NiTi may be unnecessary to promote corrosion resistance in vivo [66].…”
Section: B3 Niti Crevice and Pitting Corrosionsupporting
confidence: 57%
“…The maximum recoverable strain is about 6%. These FSMAs have the potential to be used as fast-acting actuators and in percutaneously placed implant devices [66]. The corrosion resistance of the Ni-Mn-Ga FSMAs is typically fairly poor.…”
Section: F1 Magnetic Shape Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…However, literature revealed very limited number of publications concerning corrosion behaviour of these materials. [18][19][20] In addition, and to the best of our knowledge, there are no reports in the literature concerning the effect of Al addition as an alloying element on the corrosion behaviour of CoNiGa MSMA.…”
Section: Introductionmentioning
confidence: 99%
“…The shape memory response of nitinol is 57 defined as the recovery of the material's mechanical deformation 58 when it is heated to above the transformation temperature (i.e., 59 austenite phase) from a low temperature state (i.e., martensite 60 phase) [8,9]. This shape memory behavior is beneficial in the 61 catheter-based delivery devices, because the nitinol device can 62 be easily collapsed into a small diameter catheter in its martensite 63 phase and upon exposure to blood temperature, it deploys to its 64 original shape (the austenite phase). Another unique feature of 65 nitinol is the superelasticity that provides high resistance against 66 plastic deformation during the device delivery in tortuous vascula-67 ture (i.e., kink resistance) and in the device placed in the artery or 68 vein where cyclic hemodynamic loads occur (i.e., fatigue resis- 69 tance).…”
mentioning
confidence: 98%